Implikasi Pariwisata Bencana (Disaster Tourism) Terhadap Kapasitas Masyarakat Desa Sugihwaras, Kecamatan Ngancar, Kabupaten Kediri Dalam Menghadapi Bencana - Sari, Anissa Megia; , Dr. Kuswaji Dwi Priyono, M. Si (2016)
The research with the title of "Disaster Tourism Implication towards Capacity of Sugihwaras Villagers in Ngancar istrict, Kediri Regency in Coping With a Disaster" has the objectives to examine the social and economic vulnerabilities level, community's capacity in coping with the eruption disaster, and the correlation and implication of disaster tourism activities toward communities' empowerment issues of Sugihwaras Village, Ngancar District, Kediri Regency. A question list, questionnaires, and interviews were used to collect data about social and economic vulnerabilities, communities' capacity, and the correlation and implication of disaster tourism using Snowball Sampling Method. The data was analysed by giving a score in each variable of vulnerability and capacity based on the Regulation of Head, National Disaster Management Agency (BNPB) Number 02 of 2012. The preliminary results of the research show that high-level of social vulnerability was found in Dusun Rejomulyo and Mulyorejo, meanwhile the low-level was presented in Dusun Sugihwaras. High-level of economic vulnerability was occured in Dusun Rejomulyo, medium-level was shown in Dusun Mulyorejo, and low-level was found in Dusun Sugihwaras. High-level capability of Sugihwaras Villagers was seen in Dusun Mulyorejo, while the medium-level capability of the villagers was seen in Dusun Rejomulyo and Sugihwaras. There was a high correlation between tourism activity towards community capacity, and a low correlation between tourism activities towards economics. Tourism activities in Sugihwaras Village have a role in empowering local communities through culture vibrations and disaster management those uphold the local wisdoms. We conclude that Sugihwaras Villagers are generally have good capabilities and awareness of Mount Kelud's threats. Disaster tourism has significant contribution towards communities' empowerment and capability to cope the disaster's risks and vulnerabilities.